Maize seed vigor and its effects on crop cultivation cycle. - MONDO, V. H. V. (2015)
This study aimed to investigate influences of maize seed vigor on crop cycle. Four maize seed lots with different seed vigor levels were sowed in the field and evaluated daily, computing growing-degree-days for each plot to reach each phenological stage. Differences among treatments during plant development were observed, which occurred at emergence, 4th, 8th, 12th fully expanded leaves and at milk stages. Therefore, it is possible to affirm that seed vigor has impacts on crop cultivation cycle, with plants from lower vigor seeds presenting a delayed development compared to higher vigor seeds. However, such differences tend to disappear during the reproductive phase.